Orally Administered Nanotherapeutics For Parkinson’s Disease: An Old Delivery System Yet More Acceptable - Aggarwal, Nidhi; Qamar, Zufika; Rehman, Saleha; Baboota, Sanjula; Ali, Javed (Current Pharmaceutical Design, 2020)
As per the present global scenario, Parkinson’s disease (PD) is considered to be the second most common neurodegenerative disorder which is a keen area of interest among researchers. The conventional therapies generally employed against PD are associated with serious drawbacks including limited transport across selectively permeable BBB, hepatic metabolism, intestinal barrier, etc. This urges the need to develop novel therapeutic alternatives. The oral route being the most preferred route of administration needs to be explored for new and more intelligent drug delivery systems. Nanotechnology has been proposed to play a promising role in reversing the progression of the disease via the oral route. Nanocarriers, namely nanoparticles, lipid nanoparticles, nanoemulsions, nanocrystals, nanomicellar formulations, self-nanoemulsifying drug delivery systems and alginate nanocomposites have been investigated upon to modulate the fate of drugs inside the human body when administered orally. The development of various nanotherapeutics for the treatment of PD has been reviewed, depicting an enhanced bioavailability to provide a desired therapeutic outcome. The new advances in the therapy have been explored and highlighted through the body of this review. However, a therapeutically effective concentration at the target site remains a challenge, therefore extensive exploration in the field of nanotherapeutics may facilitate superior drug delivery to CNS via oral route thereby improving the state of disease progression.
Keywords: lipid nanoparticles